(untitled) (Physical Education, Health and Social Sciences, 2025)
Low back pain is a frequent public health problem in the working population and one of the common causes of disability. It is the major cause of work-related illnesses and a worldwide most popular diagnosis for filing claims within workers’ compensation processes in low- and middle-income countries. Pakistan is a developing country, where there is a lack of working materials and unavailability of trained laborers, and a lack of knowledge about ergonomic posture. This leads to hazardous working conditions, including lifting heavy objects, prolonged standing, bending, repeated twisting, or faulty posture for extended periods without adequate breaks. Thus, the purpose of this study was to examine the prevalence of work-related low back pain and its associated risk factors among hotel and restaurant workers in Peshawar, Pakistan. To determine the prevalence of work-related low back pain and its associated risk factors among hotel and restaurant workers in Peshawar. A cross-sectional survey was conducted using the ‘Standardized Nordic Questionnaire’ adopted from a previous study conducted in Gondar town, North West Ethiopia. For the assessment of pain severity, a Numerical Pain Rating Scale (NPRS) was used. The sample includes 377 workers who were selected by a non-probability convenience sampling from hotels and restaurants in Peshawar. The data was analyzed and presented in the form of mean and SD, frequencies and percentages, and a chi-square test was performed to assess the association between the categorical variables using SPSS version 23. Out of 377 participants, 173 (45.9%) reported WR-LBP, with the highest prevalence observed among chefs/cooks 46 (12.2%), followed by waiters 42 (11.1%), managers, 33(8.8%), receptionists 30(8%) and housekeeping staff 22 (5.8%). Male workers were more commonly affected by WR-LBP than females. There is a statistically significant association between WR-LBP and sex, working experience, occupation, BMI, ergonomics training, knowledge of back ergonomics, mental stress due to work, work satisfaction, and occupational and ergonomic factors among hotel and restaurant workers (p<0.05). However, there is a clinically but not statistically significant association between WR-LBP and marital status, regular exercise, and sleep disturbance due to work (p>0.05). This study concluded that there is a high prevalence of WR-LBP among the hotel and restaurant workers, particularly the male population in Peshawar. Demographic variables, personal factors, psychological factors, and occupational and ergonomic factors are common risk factors associated with WR-LBP among hotel and restaurant workers in Peshawar.